Historical development of linguistics’ bibliography in Russia (1860-2013) - V. V. Goncharova (Библиосфера, 2016)
The interdisciplinary character of the science of language causes great difficulties in bibliographic support in this field. The object of bibliographing in linguistics is not only literature on the language, but also a variety of linguistic resources, which represent a special object to study a branch of linguistics - lexicography. Bibliography of linguistics is the least studied field by specialists among humanitarian bibliographic complexes. The paper first studied the array of domestic bibliographic sources for more than 150 years; the most significant of them are shown. The subject of research is national bibliographic resources in the linguistics field. The objective is to characterize the historical development of the linguistic bibliography in Russia. To achieve this goal we had to solve a number of tasks: identify existing sources for ongoing historical research; to trace the history of forming bibliographic sources, bibliography of bibliographies of linguistics; to form and analyze the body of bibliographic materials; to characterize the problematic areas in the bibliographic software of linguistics. Using the bibliometric analysis it was studied an array of bibliographic products published between 1860 and 2013, the dynamics of bibliographic resources formation was determined, the degree of bibliographic support of some topics and issues in linguistic science and prior directions of their development were revealed. The main results of the study should be considered: 1. The nuclear of fundamental indices on general and applied linguistics is singled out in analyzed literature sources covering the period 1918-1977, as well as in Slavic linguistics for 1825-1981. The complex of current and retrospective bibliographic products was formed and replenished in the country in 1963-1988. 2. The largest share of bibliographic sources in linguistics is presented by book and article bibliography (over 70%), many of which remain bibliographically unrecorded and unused. 3. The following subject areas of linguistics are considered to be bibliographically supported: inter-linguistics, culture of speech and language norms, lexicography, linguistic geography, linguistics regional geography, onomastics. 4. An obvious need to continue the index or database of bibliographic aids in the field of linguistics over the past 50 years is marked. 5. Further development of the linguistics bibliography is impossible to imagine without creating an electronic guide on the bibliographic resources of linguistics, which would reflect the diversity of bibliographical resources and provide their rich information potential for professionals and remote users